"It has no meaning to me." How do researchers understand the effectiveness of literature searches? A qualitative analysis and preliminary typology of understandings. (1st July 2020) - Cooper, Chris; Garside, Ruth; Varley‐Campbell, Joanna; Talens‐Bou, Juan; Booth, Andrew; Britten, Nicky
Abstract : This study aimed to address the question: what does "effectiveness" mean to researchers in the context of literature searching for systematic reviews? We conducted a thematic analysis of responses to an e‐mail survey. Eighty‐nine study authors, whose studies met inclusion in a recent review (2018), were contacted via e‐mail and asked three questions; one directly asking the question: in literature searching, what does effective (or effectiveness in) literature searching mean to you? Thirty‐eight (46%) responses were received from diverse professional groups, including: literature searchers, systematic reviewers, clinicians and researchers. A shared understanding of what effectiveness means was not identified. Instead, five themes were developed from data: (a) effectiveness is described as a metric; (b) effectiveness is a balance between metrics; (c) effectiveness can be categorized by search purpose; (d) effectiveness is an outcome; and, (e) effectiveness is an experimental concept. We propose that these themes constitute a preliminary typology of understandings. No single definition of effectiveness was identified. The proposed typology suggests that different researchers have differing understandings of effectiveness. This could lead to uncertainty as to the aim and the purpose of literature searches and confusion about the outcomes. The typology offers a potential route for further exploration.